KORELASI KESEHATAN MENTAL DAN STRES TERHADAP PEMBELAJARAN PENDIDIKAN JASMANI DI SMA KHADIJAH SURABAYA - Anas Nur Maliki; Sri Wicahyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mental health and learning stress are psychological factors that can affect students' learning process, including in Physical Education. This study aims to analyze the relationship between mental health and stress levels with the learning outcomes of 10th-grade students in SMA Khadijah Surabaya. The study used a quantitative approach with a cross-sectional design on 72 students selected through a total sampling technique. Mental health was measured using the Depression Anxiety Stress Scale-21 (DASS-21), while learning stress used the Perceived Stress Scale-10 (PSS-10). Physical Education learning outcome data were obtained through a Google Form-based evaluation. Data analysis was carried out descriptively and inferentially using the Spearman's Rho test because some of the data were not normally distributed. The results showed an average Physical Education score of 80.49 with a relatively homogeneous data distribution. In addition, no significant relationship was found between mental health or learning stress with students' Physical Education learning outcomes.